Front Cover: Chimeric Interaction of Nitrogenase‐Like Reductases with the MoFe Protein of Nitrogenase (ChemBioChem 12/2020). (27th May 2020) - Jasper, Jan; Ramos, José V.; Trncik, Christian; Jahn, Dieter; Einsle, Oliver; Layer, Gunhild; Moser, Jürgen
Abstract : The cover feature picture shows the getting together of nitrogen fixation and chlorophyll biosynthesis. Nitrogenase and the related nitrogenase‐like enzymes involved in chlorophyll biosynthesis drive crucial processes on earth. Complex formation between the catalytic component of nitrogenase (MoFe) and the nitrogenase‐like reductase (ChlL)2 indicated ATP‐dependent crosstalk, which is highlighted by a flashing handshake. The cornfield symbolizes the future perspective of transgenic plants with the ability to fix nitrogen. Nitrogenase‐like reductases might serve as a platform for the development of a more robust nitrogenase reductase. More information can be found in the full paper by J. Moser et al.